2011
DOI: 10.1051/0004-6361/201015894
|View full text |Cite
|
Sign up to set email alerts
|

The Earth’s variable Chandler wobble

Abstract: Aims. We investigated the causes of the Earth's Chandler wobble variability over the past 60 years. Our approach is based on integrating of the atmospheric and oceanic angular momentum computed by global circulation models. We directly compared the result of the integration with the Earth's pole coordinate observed by precise astrometric, space, and geodetic techniques. This approach differs from the traditional approach in which the observed polar motion is transformed into a so-called geodetic excitation fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…As their periods are close together, their addition generates a 6–7 year beat period. The annual wobble is a forced motion only, mainly by the atmosphere, while the Chandler wobble is a resonant oscillation forced by the atmosphere and the oceans (Bizouard et al, ; Plag, ). The Chandler wobble can be considered as a continuously or, at least, frequently excited, damped harmonic oscillation.…”
Section: Monitoring Geophysical Phenomenamentioning
confidence: 99%
“…As their periods are close together, their addition generates a 6–7 year beat period. The annual wobble is a forced motion only, mainly by the atmosphere, while the Chandler wobble is a resonant oscillation forced by the atmosphere and the oceans (Bizouard et al, ; Plag, ). The Chandler wobble can be considered as a continuously or, at least, frequently excited, damped harmonic oscillation.…”
Section: Monitoring Geophysical Phenomenamentioning
confidence: 99%
“…In the past, when the physical processes exciting the Chandler wobble were not fully known, the period and Q were determined by applying a statistical model of the excitation process [e.g., Jeffreys , ; Wilson and Haubrich , ; Wilson and Vicente , , ]. While the exact mechanism of Chandler wobble excitation is still under investigation, it has been shown that processes in the oceans and atmosphere are energetic enough to excite the Chandler wobble [ Gross , ; Brzeziński and Nastula , ; Brzeziński et al , ; Gross et al , , ; Liao et al , ; Bizouard et al , ; Nastula et al , ; Zotov and Bizouard , ; Gross , ]. The role of continental hydrology in polar motion excitation is not as well known as those of the atmosphere and oceans [ Dobslaw et al , , Brzeziński et al , , ; Nastula et al , , ; Seoane et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…A prominent eigen‐mode of a gigantic linear oscillator that persists in spite of the three shortages is the Chandler Wobble: a supposedly free circular eigen‐wobble by the Earth's rotational axis around the axis of spheroidal symmetry at a period of ≈433 days (e.g., refs. [1–6]). Related but a little more complicated than a 1D oscillator is the phenomenon of the Earth's background noise known as the hum, that is, irregular but persistent oscillations detected by superconducting gravimeters in a very quiet environment.…”
Section: Introductionmentioning
confidence: 99%